A forensic entomology case from the Amazon rain forest of Brazil - Pujol-Luz, J. R.; Marques, Helder; Ururahy-Rodrigues, Alexandre; Rafael, José Albertino; Santana, Fernando H.A.; Arantes, Luciano C.; Constantino, Reginaldo (Journal of Forensic Sciences, 2006)
The first case of application of forensic entomology in the Brazilian Amazonia is described. The corpses of 26 men were found in the rainforest in Rondonia State, Brazil. Fly larvae collected on the bodies during autopsy were identified as Paralucilia fulvinota (Diptera, Calliphoridae). No data or specimens were collected at the crime scene. At the laboratory, the larvae developed into pupae in 58 h and into adults in 110.5 h. The total development time for P. fulvinota was measured in field experiments inside the forest. The age of the larvae when collected from the bodies was estimated as the difference between the time required for them to become adults and the total development time for this species. The estimated age of the maggots and the minimum postmortem interval was 5.7 days. Copyright © 2006 by American Academy of Forensic Sciences.
Keywords: Autopsy; Data Analysis; Fly; Forensic Identification; Forest; Human; Larva; Nonhuman; Priority Journal; Animal; Diptera; Entomology; Forensic Anthropology; Humans; Larva; Male; Postmortem Changes; Tropical Climate